The portrayal of Abkhazia in the memoir of Babo Sharvashidze - Vakhania, Nino (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
Memories, diaries, and personal correspondences have long ceased to be considered a marginal genre, as the readers’ interest in this form of literature continues to grow worldwide. The memoirs of Babo Sharvashidze, the youngest daughter of Mikheil Sharvashidze, the last prince of Abkhazia, were translated from English by Maya Tsertsvadze and published as a book in 2019 by the „Artanuji“ publishing house. According to the „Memoirs“, the author’s personal qualities, as well as the social circles, environments, and societies with whom she interacted, are extensively depicted. Babo Sharvashidze’s life spanned multiple countries, where she encountered numerous distinguished individuals and families from various nationalities including Georgian, Russian, Abkhaz, English, and others. Her memoirs encompass documentary facts and intricate details that hold immeasurable historical significance. Of particular note are the years of childhood documented in the diaries, providing a reflection of life in our beloved Abkhazia and shedding light on the experiences of a prominent and influential family. Throughout the narrative, names of geographical locations such as Likhni, Sukhumi, Ochamchire, New Athons, and others are intertwined. The vivid portrayal of Babo Sharvashidze’s parents and siblings in her memory holds great significance. It becomes evident how Russia played a role in the dissolution of the principality of Abkhazia, while also highlighting that the European way of life was not foreign or unacceptable to the small nation of Georgia; rather, it was internalized. Despite being separated from Abkhazia in her childhood due to unforeseen circumstances, the author never forgot her homeland, which is reflected in her memoirs.